Convergent Loss of ABC Transporter Genes From Clostridioides difficile Genomes Is Associated With Impaired Tyrosine Uptake and p-Cresol Production - Steglich, Matthias; Hofmann, Julia D.; Helmecke, Julia; Sikorski, Johannes; Spröer, Cathrin; Riedel, Thomas; Bunk, Boyke; Overmann, Jörg; Neumann-Schaal, Meina; Nübel, Ulrich (Frontiers in Microbiology, 2018)
We report the frequent, convergent loss of two genes encoding the substrate-binding protein and the ATP-binding protein of an ATP-binding cassette (ABC) transporter from the genomes of unrelated Clostridioides difficile strains. This specific genomic deletion was strongly associated with the reduced uptake of tyrosine and phenylalanine and production of derived Stickland fermentation products, including p-cresol, suggesting that the affected ABC transporter had been responsible for the import of aromatic amino acids. In contrast, the transporter gene loss did not measurably affect bacterial growth or production of enterotoxins. Phylogenomic analysis of publically available genome sequences indicated that this transporter gene deletion had occurred multiple times in diverse clonal lineages of C. difficile, with a particularly high prevalence in ribotype 027 isolates, where 48 of 195 genomes (25%) were affected. The transporter gene deletion likely was facilitated by the repetitive structure of its genomic location. While at least some of the observed transporter gene deletions are likely to have occurred during the natural life cycle of C. difficile, we also provide evidence for the emergence of this mutation during long-term laboratory cultivation of reference strain R20291.